IMPLEMENTASI PELATIHAN BERBASIS TEKNOLOGI DALAM PRAKTIK KERJA GURU DI SDN KOLURSARI I BANGIL - Sofiyatuz Zahroh; Suyanto Suyanto; A. Faizin (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the implementation of technology-based training in teachers’ professional practices at SDN Kolursari I Bangil and to understand its impact on improving teachers’ pedagogical competence and professionalism. The issue explored arises from the urgent need for digital adaptation in primary education, particularly amid limited resources and technological literacy in semi-urban schools. This research employed a qualitative approach using a case study design, allowing for an in-depth exploration of teachers’ real-life experiences in applying the outcomes of technology training. Data were collected through semi-structured interviews, participatory observations, and document analysis, involving three key participants: Nur Lailah (Grade 1 Teacher), Suhartono (Grade 5 Teacher), and Bahrul Ulum (Grade 6 Teacher). The findings revealed five main themes: (1) increased digital awareness and teacher motivation, (2) limited infrastructure and time constraints in technology implementation, (3) collaboration among teachers as a form of professional support, (4) the need for post-training mentoring, and (5) pedagogical transformation toward interactive technology-based learning. The implementation of training effectively enhanced teachers’ ability to use digital media such as Wordwall, Quizizz, and Google Forms, although its effectiveness remains constrained by technical and institutional support.